Impact of the Advanced Metering Infrastructure (AMI) Program on Non-Technical Losses at Distribution System - Sinurat, David Daniel Christianto; Husnayain, Faiz (International Journal of Computer and Information System (IJCIS), 2025)
The implementation of Advanced Metering Infrastructure (AMI) is a strategic initiative by PT PLN (Persero) UP3 Bandengan to support digital transformation and enhance efficiency in the electricity distribution system, particularly in reducing non-technical Losses. This study aims to evaluate the impact of AMI implementation on improving meter reading accuracy, managing customer arrears, and detecting electricity misuse. The deployed AMI system includes 142,083 single-phase and 10,278 three-phase smart meters, with connectivity rates to the Meter Data Management System (MDMS) reaching 99.36% and 99.60%, respectively. A total of 1,190 Data Concentrator Units (DCUs) have been installed to enable automatic meter reading, achieving a success rate of 96.65%. Remote disconnection and reconnection processes via MDMS recorded success rates of 97.14% and 98.65%, respectively, while anomaly current detection—used as an indicator of energy misuse—achieved an effectiveness rate of 23.87%. The findings show that AMI implementation resulted in operational cost savings of IDR 245,792,276 in manual meter reading and IDR 7,807,696,000 in arrears-related disconnections. These results highlight the significant contribution of AMI in promoting a transparent, efficient, and reliable electricity distribution system.